203k views
4 votes
Answer this pls !!!.... and thanx !

Answer this pls !!!.... and thanx !-example-1
User Wjtk
by
5.2k points

2 Answers

4 votes

Answer:

- 6x + 12

Explanation:

Expand the product of factors

= 2x² - 12x + 3x - 18 - 2x² + 3x + 30 ← collect like terms

= (2x² - 2x²) + (- 12x + 3x + 3x) + (- 18 + 30) ← simplify parenthesis

= 0 + (- 6x) + (12)

= - 6x + 12

User Mohan Noone
by
4.6k points
2 votes

This is the order you need to use to solve this problem: PEMDAS

(Parentheses, Exponents, Multiplication, Division, Addition, Subtraction)

So you start with P and make your way down to S

(2x + 3)(x - 6) - 2x² + 3x + 30 First multiply (2x + 3)(x - 6) (distribute)

(2x)x - (2x)6 + (3)x - (3)6 = 2x² - 12x + 3x - 18 = 2x² - 9x - 18

(2x²- 9x - 18) - 2x² + 3x + 30 Simplify by combining like terms

-6x + 12

User CpnCrunch
by
5.3k points